Characterisation of penetration grade 60/70 asphalt binder obtained from different suppliers - Atheer Muhammed Ali Jasim, 1986-, author; Norhidayah Abdul Hassan, supervisor; Ramadhansyah Putra Jaya, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Kejuruteraan (Pengangkutan)) - Universiti Teknologi Malaysia, 2019